2020
DOI: 10.3389/fped.2020.591693
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Mesenchymal Stromal Cell as Therapy in Neonatal Diseases

Abstract: Mesenchymal stromal cells (MSCs) can be derived from various tissue sources, such as the bone marrow (BMSCs), adipose tissue (ADSCs), umbilical cord (UC-MSCs) and umbilical cord blood (UCB-MSCs). Clinical trials have been conducted to investigate the potential of MSCs in ameliorating neonatal diseases, including bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH) and necrotizing enterocolitis (NEC). In preclinical studies, MSC therapy has been tested for the treatment of various neonatal diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 99 publications
0
25
0
Order By: Relevance
“…Examples of multipotent cells are hematopoietic stem cells (HSCs) and MSCs. HSCs can be isolated from peripheral blood, bone marrow, and umbilical cord blood, whereas MSCs can be found in bone marrow, umbilical cord, cord blood, placental, peripheral blood, adipose tissue, dental tissues, skin, salivary gland, and synovial fluid [29][30][31][32]. Although there are variations in molecular composition, surface antigen expression, differentiation capacity, and immunomodulatory property in MSCs isolated from different tissue sources [23,33], however, functional analyses showed that all the secretome have similar functionality, i.e., to promote cell migration and inhibit cell apoptosis [34] However, many studies have found that these mechanisms are insufficient, and MSCs seem to secrete a myriad of paracrine factors, e.g., growth factors, chemokines, and cytokines, to promote tissue regeneration and modulate the immune response.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Examples of multipotent cells are hematopoietic stem cells (HSCs) and MSCs. HSCs can be isolated from peripheral blood, bone marrow, and umbilical cord blood, whereas MSCs can be found in bone marrow, umbilical cord, cord blood, placental, peripheral blood, adipose tissue, dental tissues, skin, salivary gland, and synovial fluid [29][30][31][32]. Although there are variations in molecular composition, surface antigen expression, differentiation capacity, and immunomodulatory property in MSCs isolated from different tissue sources [23,33], however, functional analyses showed that all the secretome have similar functionality, i.e., to promote cell migration and inhibit cell apoptosis [34] However, many studies have found that these mechanisms are insufficient, and MSCs seem to secrete a myriad of paracrine factors, e.g., growth factors, chemokines, and cytokines, to promote tissue regeneration and modulate the immune response.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Transplantation of bone marrow mesenchymal stem cells pretreated with lipopolysaccharide can regulate the immune response in septic mice and reduce inflammation ( 70 ). adipose mesenchymal stem cells (AD-MSCs) pretreated with eicosapentaenoic acid can reduce lung and distal organ damage, improve sepsis and increase the survival rates in cecal ligation and perforation(CLP)-induced experimental sepsis ( 71 ). Systemic administration of mesenchymal stem cells pretreated with interleukin-1β (β-mesenchymal stem cells) is more effective than untreated mesenchymal stem cells in improving the symptoms of sepsis in mice and increasing the survival rate.…”
Section: Therapeutic Effects Of Mscs After Pretreatment and Genetic Modificationmentioning
confidence: 99%
“…MSCs have self-renewal, differentiation, anti-apoptotic, anti-fibrotic, pro-mitotic, anti-oxidative, and immunomodulatory properties. [86][87][88] Besides, MSCs can be harvested from many tissue sources using minimally invasive techniques. 89 MSCs can also be expanded easily for many passages without significant changes in characteristics and functionality, and produce more exosomes.…”
Section: Source Of Exosomesmentioning
confidence: 99%